2022
DOI: 10.1186/s12995-022-00351-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory afflictions during hairdressing jobs: case history and clinical evaluation of a large symptomatic case series

Abstract: Objectives Respiratory symptoms at work are common among hairdressers. Various working materials, most notably bleaching ingredients such as ammonium persulfate, have been made responsible. The objective of this study is to achieve a better understanding of work-related respiratory symptoms of hairdressers by describing common features in a large affected collective. Methods One hundred forty-eight hairdressers with respiratory symptoms at work pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Hairdressers are among the higher-risk occupational groups for respiratory problems due to unsafe working conditions, a lack of training and awareness, the use of different chemicals, a lack of regular monitoring and inspections and poor accessibility and use of PPE 15 38–41. In addition, this group of workers belongs to the informal economy, in which work-related exposure is unregulated and working conditions are substandard.…”
Section: Discussionmentioning
confidence: 99%
“…Hairdressers are among the higher-risk occupational groups for respiratory problems due to unsafe working conditions, a lack of training and awareness, the use of different chemicals, a lack of regular monitoring and inspections and poor accessibility and use of PPE 15 38–41. In addition, this group of workers belongs to the informal economy, in which work-related exposure is unregulated and working conditions are substandard.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to bleaching products was shown to be the most important factor for the development of respiratory symptoms, lung function decline and leaving the profession. In their retrospective descriptive study on 148 hairdressers with respiratory symptoms at work, Hiller et al [23] showed that 30% had changed jobs or were on longer sick leave. Sixty percent of patients had evidence of an obstructive lower airway disease and 15% were considered to have ammonium persulfate induced OA.…”
Section: Hairdressingmentioning
confidence: 99%
“…However, pathophysiological mechanism(s) of respiratory inflammation caused by PS are not yet clarified. Beside non-specific immunological pathways including chemical irritation with possible epithelial damage and histamine liberation, specific immunological reactions like IgE- or non-IgE-mediated immediate types of allergic reactions were suggested [ 8 •, 36 ]. Diagnostic procedures in this respect are, so far, hampered by the lack of commercially available standardized APS/PPS preparations for skin prick testing (SPT), and standardized reagents and methods for measuring specific IgE to PSs.…”
Section: Respiratory Sensitizationmentioning
confidence: 99%
“…SPT results vary between studies, mostly being negative in hairdressers with respiratory disorders. Recently, among 148 hairdressers seen in a German occupational medicine university clinic between 2012 and 2019, positive SPT to APS with clinical relevance was found in 15% [ 36 ]. Specific IgE antibodies to PSs have been measured even more rarely, only with “in-house” methods, and yielding positive results sporadically [ 37 , 39 ].…”
Section: Respiratory Sensitizationmentioning
confidence: 99%